An Indonesian National English Textbook for Secondary Level: Is It Qualified Enough? - Susiati, S; Mufidati, Elok (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2020)
This study describes how a national English textbook entitled When English Rings a Bell for Junior High School Level meets criteria of Cunnignswirth’s good English textbook. Interviews with the teacher and students of grade VII at SMP Muhammadiyah 10 Surakarta were conducted to investigate how the textbook is considered qualified. Document review was also applied to analyse the textbook. The results show that all chapters in the “When English Rings a Bell” textbook fulfill the Cunningsworth’s criteria of a good textbook. The textbook was suitable enough to be used for media in teaching learning process for the seventh grade students of Junior High School. From the teacher’s view, the textbook is appropriate with the learning objectives of the curret curriculum. This is in line woth the Cunningsworth’s criteria. However, some students found difficulties in using this textbook: 1). they still need teacher’s role to clearly explain the materials, 2). Supporting materials from other sources to improve the students’ ability in both comprehending the concept and doing practices. These two may be caused by the lack of examples in the textbook.